Professor reflexivo no Brasil : uma análise do conceito nos documentos de formação docente e suas implicações - Gasparini, Camile (2017)
The reflections of this dissertation are about the arrival of the reflexive teacher concept in Brazil and his reception as a teacher training proposal. The problem in question lies in the need to rethink the training in the context of prevailing education. After all, how to form reflexive teachers in the contemporary society? In this sense, the purpose is to investigate the concept´s perspective in the main educational documents (GLNEB, ONEC, NEP, Opinion NCE /FC 2/2015) and the presence/absent of this concept in the academy production and, moreover, point signs to the initial and continuing training, in special, to the University e its relation with the school. For this purpose, it was used as methodology the bibliographical and documentary qualitative survey, through the theoretical support from authors such as Dewey (1959), Schön (2000), Nóvoa (1995), Alarcão (1996) e Pimenta (2012). The contributions of this study allow to undestand the need to continue searching the field of the teachers training, however, on the optic of other themes, like the reflexive teacher. Then, it is possible to consider that the formation forward to the survey is primordial to the teacher´s future and to the investigation of his own practice, in which the pedagogical experiences become study object and enable the construction of the teaching identity. Through his identity, the professional starts to recognize himself and to be recognized by the knowledge built in the dialogue with the knowledge. Therefore, it is understood that the reflexive formation purpose implies a change of formative paradigm, a closer approximation between university and school to rethink the relation survey/formation, besides requiring educational politics that value the knowledge and the teacher´s profession, allowing reflexive spaces within the educational institutions.